THE COMPARISON OF HEALTH STATUS AND INDEPENDENCE BETWEEN THE ELDERLY IN THE NURSING HOMES AND LIVING WITH FAMILY - Retno Setyowati; Mujahidatul Musfiroh; Istar Yuliadi; Desiderius Priyo Sudibyo; Trisni Utami (Placentum, 2023)
Background: The elderly period is a gift in human life because not all humans can experience this period. The elderly period experience changes in anatomical and physiological functions, so the elderly are very vulnerable to health problems. Many factors cause health problems in the elderly, including decreased function of the elderly and elderly health problems that can affect the independence of the elderly in carrying out daily activities. This study aims to describe the health status and independence of the elderly in nursing homes and living with their families.